Natural Antimicrobials in Food Safety and Quality - Rai, Mahendra (CABI, 2014)
The demand of producing high-quality, safe (pathogen-free) food relies increasingly on natural sources of antimicrobials to inhibit food-spoilage organisms and food-borne pathogens and toxins. The discovery and development of new antimicrobials from natural sources for a wide range of applications requires that knowledge of traditional sources for food antimicrobials is combined with the latest technologies in identification, characterization and application. This book explores some novel, natural sources of antimicrobials as well as the latest developments in using well-known antimicrobials in food. The book includes antimicrobials from microbial sources (bacteriophages, bacteria, algae and fungi), animal-derived products (milk proteins, chitosan and reduction of biogenic amines), plants and plant products (essential oils, phytochemicals and bioactive compounds). A separate section of the book covers natural antimicrobials for fresh products. New and emerging technologies (a database for bacteriocin and predictive modelling of antimicrobial efficacy) concerning antimicrobials have also been incorporated. The book could be considered essential reading for food technologists, microbiologists, biotechnologists, pharmacologists, botanists, agriculture specialists and those who believe in eco-friendly natural products. It should also be useful for postgraduate students and researchers. We are grateful to all the contributors for the submission of their valuable manuscripts. Mahendra Rai wishes to thank Aniket Gade, Alka Karwa, Ravindra Ade, Avinash Ingle, Dhyaneshwar Rathod, Alka Yadav, Vaibhav Tiwari, Jayendra Kesharwani, Swapnil Gaikwad, Shital Bonde, Sonal Birla and Shivaji Deshmukh for help in editing. The editors wish to thank Sarah Mellor for her encouragement and help in bringing out the book in the present form. We also thank Dr Geetika Sareen for suggestions during publication of the book.